(untitled) (Indonesian Journal of Technology and Computer Science, 2025)
The Ministry of Maritime Affairs and Fisheries oversees the Depok Ornamental Fish Cultivation Research Institute (BRBIH), a research organization that supports research endeavors and community empowerment by providing public facilities like fields, halls, and guest house messes. However, there are a number of issues with the manual reservation procedure, including inefficient use of time, inaccurate recording, a lack of real-time facility availability information, and a delayed validation time for reservation requests. By applying the Scrum approach, this project seeks to design and develop a facility reservation application that is effective, structured, and responsive to user needs on many platforms (web and mobile). Direct observation, BRBIH official interviews, and literature reviews were used to gather data. A MySQL database, a Bootstrap-based interface with Tabler.io, the PHP programming language, and the CodeIgniter 4 framework were used to create the application. The development outcomes demonstrate that the Scrum methodology enhances the quality of BRBIH’s public services, promotes process flexibility, and speeds up adaptability to system requirements. By offering centralized reservation recording, automated notifications, and real-time facility information, the system increases user happiness and management effectiveness.